Mengidentifikasi Masalah Sosial Di Masyarakat Dan Mengetahui Teknik Mengatasinya Melalui Sebuah Kajian Literatur - Qomariah, Amini Isti; Juliansyah, Syafana Candra; Haq, Alifia Tarijul; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Abstract. Social problems are a complex issue that continues to occur among society, specifically in Indonesia. Social issues needs consideration by every structure in society, both the government and society itself. To begin, this paper will look into the topic about the method to identify a social issues that occurs and techniques for solving it, so every structure of society can resolve or even anticipate the social issues around them. The research method used in this paper is a literature review obtained from several studies regarding the identification of social issues and techniques for solving them carried out by previous researchers so that the paper presented is supported by valid data.